Evolution of Hypervariable Region 1 of Hepatitis C Virus in Primary Infection - Manzin, Aldo (American Society for Microbiology, 1998)
The hypervariable region 1 (HVR-1) of the putative envelope encoding E2 region of hepatitis C virus (HCV) RNA was analyzed in sequential samples from three patients with acute type C hepatitis infected from different sources to address (i) the dynamics of intrahost HCV variability during the primary infection and (ii) the role of host selective pressure in driving viral genetic evolution. HVR-1 sequences from 20 clones per each point in time were analyzed after amplification, cloning, and purification of plasmid DNA from single colonies of transformed cells. The intrasample evolutionary analysis (nonsynonymous mutations per nonsynonymous site [K(a)], synonymous mutations per synonymous site [K(s)], K(a)/K(s) ratio, and genetic distances [gd]) documented low gd in early samples (ranging from 2.11 to 7.79%) and a further decrease after seroconversion (from 0 to 4.80%), suggesting that primary HCV infection is an oligoclonal event, and found different levels and dynamics of host pressure in the three cases. The intersample analysis (pairwise comparisons of intrapatient sequences; rK(a), rK(s), rK(a)/rK(s) ratio, and gd) confirmed the individual features of HCV genetic evolution in the three subjects and pointed to the relative contribution of either neutral evolution or selective forces in driving viral variability, documenting that adaptation of HCV for persistence in vivo follows different routes, probably representing the molecular counterpart of the viral fitness for individual environments.